Polish and Ukrainian universities cooperation for pursuing professional learning level - Kuk, Tomasz (Professional Pedagogics, 2017)
The article raises questions about challenges for professional education. How much is it adapted to the changes of an environment? What goals should be set for it in coming years? How to join this global community to benefit from its resources? World Class University is an idea that can connect universities independently of their potential and resources by giving synergistic cooperation. At the same time, it provides greater competitiveness in the educational market, giving invaluable opportunities to migration of knowledge, experience, and common research efforts. The main beneficiary of these processes should be a student. His plans and intentions, awareness of the role which he wants to play in the future in the labour market, and the goals he sets for himself. Adaptation of the new quality education to the needs of this group is an absolutely essential factor for improving the quality of higher-degree education to the more practical and international degree relating requirements. The main aim of this article is to analyse students’ readiness, in Poland and Ukraine, to achieve professional success, its resources and readiness of universities to participate in occupational and scientific development. This means creating a «World University» in the context of Poland and Ukraine, that has an impact on creating a world-class graduate, who will be known on international labour market. The article presents suggestion for such an action.